2008
DOI: 10.1021/ie800106e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structure Type of Al2O3 on Dehydration of Methanol for Dimethyl Ether Synthesis

Abstract: This study focused on the effect of alumina properties on the catalytic performance in the dehydration of methanol to synthesize dimethyl ether. The catalysts (γ-Al 2 O 3 and η-Al 2 O 3 ) were prepared from boehmite and bayerite, respectively, via calcination at various temperatures. With heat treatment, the properties of alumina have been changed significantly. Under identical reaction conditions, γ-Al 2 O 3 calcined at 500°C and η-Al 2 O 3 calcined at 600°C showed the highest catalytic activity, because of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…For all catalysts, the particle size of γ-Al 2 O 3 increased with increasing calcination temperature which is in agreement with Seo et al [27]. The large particle size for the AN120,…”
Section: X-ray Diffraction (Xrd) Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…For all catalysts, the particle size of γ-Al 2 O 3 increased with increasing calcination temperature which is in agreement with Seo et al [27]. The large particle size for the AN120,…”
Section: X-ray Diffraction (Xrd) Analysissupporting
confidence: 91%
“…Seo et al [27] studied the influence of structure type of Al 2 O 3 on the dehydration of methanol to dimethyl ether. Catalysts (γ-Al 2 O 3 and η-Al 2 O 3 ) were prepared from boehmite and bayerite, respectively, via calcination at various temperatures and the effect of alumina properties on the catalytic performance evaluated.…”
Section: Furthermore Diesel Exhausts Have Been Linked To Cancer [1] Imentioning
confidence: 99%
See 2 more Smart Citations
“…It have been known that the moderate acid site strength of alumina could enhance the formation of DME from methanol. 13 In our previous work, 14 η-Al 2 O 3 showed significant performance for methanol dehydration to produce DME. Moreover, it was found that the structure of alumina is more crucial factor than acidity properties to determine catalytic performance.…”
Section: Introductionmentioning
confidence: 88%